Peran Event Account Executive Dalam Mengelola Administrasi Event di Event Organizer Setrise Culture - syahira, nandita; Syah, Firman (Bisnis Event, 2024)
The event organizer services industry in Indonesia has experienced rapid growth, driven by increasing client interest in event management. Event administration is crucial to ensuring the smooth operation and success of events. Event Account Executives play a pivotal role as liaisons between the company and clients or sponsors, responsible for collecting partnership data, preparing reports, and conducting final event evaluations. Post-pandemic, the MICE (Meetings, Incentives, Conferences, Exhibitions) industry has shown significant growth, with special events being integral to MICE activities. This study poses several key questions regarding preparation, implementation, challenges, and solutions faced by Event Account Executives in managing event administration at Setrise Culture. Data collection methods include fieldwork, browsing, insights from authorities, observations, and relevant documents. Data is analyzed using a qualitative descriptive approach to depict facts, situations, and perspectives relevant to the role of Event Account Executives. The purpose of this report is to deepen understanding of the pivotal role played by Event Account Executives in the event organizer industry, offering insights for practitioners and researchers. This study aims to enhance knowledge for the author, contribute to academic understanding, and provide practical guidance for companies seeking to optimize the role of Event Account Executives to achieve internal goals and client satisfaction.Top of Form Keyword: special event, account executive, MICE, event organizer.